Fungal differentiation: a model phenomenon to screen antifungal drugs - Pathan, E.K.; Tupe, S.G.; Deshpande, M.V. (Developments in Fungal Biology and Applied Mycology, 2017)
Pathogenic fungi change the morphology to a suitable vegetative form such as unicellular yeast or filamentous mycelium for the survival and proliferation in the host as well as to defeat cellular and physiological defences of the host. The microenvironment of the pathogen triggers different biochemical processes finally leading to differentiation. These biochemical processes, which correlate with morphological change from saprophytic/less virulent to pathogenic form, can be targeted for the development of novel antifungal agents. The present chapter deals with the role of differentiation in fungal pathogenesis and discusses different biochemical events as target for the antifungal strategies.